Hypoxia and Performance 2024: A project arising from “questions from the field” to improve scientific support in the area of environmental stress - Brocherie, Franck; Brugniaux, Julien; Connes, Phillipe; Dufour, Stéphane; Gaston, Anne-Fleur; Gimenez, Philippe; Millet, Grégoire P.; Nader, Elie; Pichon, Aurélien; Robach, Paul; Woorons, Xavier (Réflexions Sport, 2024)
Since Mexico Olympic Games 1968, technological and scientific advancements have contributed to the development of various altitude/hypoxic training methods, which have proven beneficial for different Olympic disciplines. However, aspects such as method planning, monitoring of hypoxic dose, training load, fatigue and their respective individual variability remain under-researched. The HYPOXPERF project, developed in collaboration with the federations involved, is contributing to the advancement of scientific knowledge by providing new insights into the identification of individual responses, the validity of combined methods and cross-adaptations. The project has facilitated the refinement of practical recommendations and has also led to the emergence of new demands for monitoring, scientific support and research in the lead-up to the upcoming Summer and Winter Olympic Games (Los Angeles 2028, Cortina 2026, and French Alps 2030), with opportunities for transfer to the general public in terms of health and well-being.